2019
DOI: 10.5539/ijb.v11n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Ants' Notion of Zero through the Perception of the Absence of an Odor

Abstract: Workers of the ant Myrmica sabuleti can acquire the notion of ‘nothing’, i.e. a basic concept of zero, through olfactory conditioning, the best when the odor is unpleasant (onion odor) and when the response to the absence of the odor is rewarded. With a pleasant odor (lavender, rosemary or vanilla odor), the ants learn best when the response to the odor is rewarded. To our knowledge this is the first time that olfactory operant conditioning is obtained in animals by rewarding their response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Using six ant colonies and making three different experiments, we found that these insects mentally situated the smaller amounts of elements on the left of larger ones, and the larger ones on the right of smaller ones, this including the zero element. This result is in agreement with the finding that the workers of the ant M. sabuleti locate the zero at the start of an increasing series of elements and at the end of a decreasing series of elements (Cammaerts & Cammaerts, 2019e). We here can add that, for the ants, the zero is the 'most to the left' value.…”
Section: Discussion -Conclusionsupporting
confidence: 92%
“…Using six ant colonies and making three different experiments, we found that these insects mentally situated the smaller amounts of elements on the left of larger ones, and the larger ones on the right of smaller ones, this including the zero element. This result is in agreement with the finding that the workers of the ant M. sabuleti locate the zero at the start of an increasing series of elements and at the end of a decreasing series of elements (Cammaerts & Cammaerts, 2019e). We here can add that, for the ants, the zero is the 'most to the left' value.…”
Section: Discussion -Conclusionsupporting
confidence: 92%
“…It has been shown that bees have the notion of zero and correctly locate the zero in an increasing as well as in a decreasing series of numbers (Howard, Avarguès-Weber, Garcia, Greentree, & Dyer, 2018). In ants, besides having pointed out that M. sabuleti workers can distinguish different numbers of elements (Cammaerts, 2008), we have also shown that they have a basic notion of zero using their visual as well as their olfactory perception (Cammaerts & Cammaerts, 2019a, 2019b. Here, we intended to work again on colonies of M. sabuleti, presenting them either 1 + 1, or 2 + 1, or 3 + 1, or 3 + 2 elements, and looking if they could, each time, add the two presented numbers of elements, i.e.…”
Section: Introductionmentioning
confidence: 61%
“…It has been shown that rhesus monkeys (Merritt, Rugani, & Brannon, 2009) and humans (Pinhas & Tzelgov, 2012) locate the zero on a number line, and ordered it at the start of a numerical continuum. Concerning the ant species here studied, its workers locate the zero at the start of an increasing series of elements as well as at the end of a decreasing series of elements (Cammaerts & Cammaerts, 2019c), and since these ants have a left to right oriented number line (Cammaerts & Cammaerts, 2019d), it can be deduced that they locate the zero on the left, just at the beginning of their number line.…”
Section: Discussion Conclusionmentioning
confidence: 83%
“…Indeed, when studying the ants' notion of zero (Cammaerts & Cammaerts, 2019a), we found a conditioning score of 82.5% for the ants' discrimination between 2 and 1 circles. When studying the ants' correct location of the zero (Cammaerts & Cammaerts, 2019c), we found a conditioning score of 83.3% for the discrimination of 2 vs 1 elements (mean ants' response: 4.0 vs 0.8), and a conditioning score of 82.6% for the discrimination of 1 vs 2 elements (mean ants' response: 3.8 vs 0.8). When studying the ants' arrangement of numbers on their number line (Cammaerts & Cammaerts, 2020a), we found a conditioning score of 83.4% for the ants' discrimination of 1 vs 2 elements, during their first 48 training hours.…”
Section: Discussion Conclusionmentioning
confidence: 87%